Bioactive glass containing 90% SiO2 in hard tissue engineering: An in vitro and in vivo characterization study. (10th July 2019) - Lehman, Luiz Felipe Cardoso; de Noronha, Mariana Saturnino; Diniz, Ivana Márcia Alves; da Costa e Silva, Rosangela Maria Ferreira; Andrade, Ângela Leão; de Sousa Lima, Luiz Fernando; de Alcântara, Carlos Eduardo Pinto; Domingues, Rosana; Ferreira, Anderson José; da Silva, Tarcília Aparecida; Mesquita, Ricardo Alves
Abstract: Bioactive glass has been proved to have many applications in bioengineering due to its bone regenerative properties. In this work, an innovative, highly resorbable bioactive glass containing 90% SiO2 (BG90) to be used as a bone substitute was developed. The BG90 was synthetized by the sol–gel process with the dry step at room temperature. The biomaterial showed in vitro and in vivo bioactivities even with silica content up to 90%. Moreover, the BG90 presented high porosity and surface area due to its homogenously interconnected porous network. In vitro, it was observed to have high cell viability and marked osteoblastic differentiation of rat bone marrow‐derived cells when in contact with BG90 ion extracts. The BG90 transplantation into rat tibia defects was analysed at 1, 2, 3, 4, 7, and 10 weeks post‐operatively and compared with the defects of negative (no graft) and positive (autogenous bone graft) controls. After 4 weeks of grafting, the BG90 was totally resorbed and induced higher bone formation than did the positive control. Bone morphogenetic protein 2 (BMP‐2) expression at the grafting site peaked at 1 week and decreased similarly after 7 weeks for all groups. Only the BG90 group was still exhibiting BMP‐2 expression in the last experimental time. Our data demonstrated that the BG90 could be an attractive candidate to provide useful approaches in hard‐tissue bioengineering.